ON THE SIGNIFICANCE OF ALISHER NAVOI’S WORK IN WORLD LITERATURE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article talks about the interest in the works of Alisher Navoi throughout the world, about the translations of the works of the great poet into many languages of the world, about the deep philosophy of his work, about the secret of the unfading glory of Navoi's works.